Combating challenges in CAR-T cells with engineering immunology - Wang, Clement Yisai; Ting Cheung, Stephanie Po; Sugimura, Ryohichi (Frontiers in Cell and Developmental Biology, 2022)
Chimeric antigen receptors (CAR) T cells (CAR-T) mark a major step towards producing safe and effective personal anticancer treatments. CAR-T strategies engineers the T cells from the patients to allow specific binding to a tumor-specific antigen. Though showing effective antitumor abilities in multiple hematological malignancies and solid tumor cancers, the issues of antigen escape, tumor infiltration/penetration, and toxicity side effects, limits the usage of prolonged CAR-T therapies. Engineering immunology has exploited human stem cell-based CAR-T therapies and the development of CAR-M (macrophage) therapies to combat the disadvantages of conventional CAR-T therapies. In this review, we will highlight the challenges of CAR-T therapies and combat them with engineering immunology for cancer immunotherapy.